Debating the Place of Yiddish in the Romanian Jewish Education System During the Interwar Period: Perspectives from Jewish Elites and Romanian Authorities. - Nastasă-Matei, Irina (Shofar: An Interdisciplinary Journal of Jewish Studies, 2024)
The article discusses the debates surrounding the use of Yiddish as a language of education in Jewish schools in Greater Romania during the interwar period. Various Jewish elites and Romanian authorities had conflicting views on the matter, with Jewish leaders from different regions and political orientations advocating for either Yiddish or Hebrew. The Romanian authorities implemented laws aimed at Romanianizing the education system, which impacted Jewish schools, leading to challenges and restrictions on teaching in Yiddish. The article highlights the diverse linguistic identities and educational traditions of Jewish communities in different regions of Greater Romania, shedding light on the tensions and conflicts surrounding the use of Yiddish in Jewish education.